Benchmarking Whole‐Body Controllers on the TALOS Humanoid Robot - Ramuzat, N.; Stasse, O.; Boria, S. (Frontiers in Robotics and AI, 2022)
This paper presents a comparison of three control schemes applied on the commercially available TALOS Humanoid Robot. The aim is to highlight the advantages and drawbacks of each model applied on three locomotion problems: walking on flat and non-flat terrain and climbing stairs. The different models are based on position control (first and second models) or torque control (third model). The first one uses a hierarchical quadratic program at velocity level. The second one employs a weighted quadratic program named Task Space Inverse Dynamic (TSID) at acceleration level. Finally, the last one also uses TSID but at torque level. The controllers performances are compared in simulation, using Gazebo, on the accuracy of their tracking, their energy consumption and their computational time execution.